Analisis Perlakuan Akuntansi Goodwill dalam Kombinasi Bisnis: Kajian PSAK 22 dan Implementasinya di Indonesia - M. Masrukhan; Nurul Fadlilah; Anggaraslasi; Dini Nenawati (Master Manajemen, 2024)
Accounting regulates how an entity runs properly in accordance with existing regulations, one example of which is the accounting treatment in business combinations. Accounting regulates how business combinations occur by referring to standards or regulations, one of which is contained in PSAK 22 which discusses business combinations. The discussion of PSAK 22 also explains how accounting treats the goodwill of an entity. The aim of this analysis is for us to understand how accounting treats business combinations where there is goodwill or added value from various aspects, including loyalty, good name and so on. Writing research in this journal uses a library research approach and method, using qualitative methods sourced from literature, scientific articles, or other supporting documents. Generally, business combinations are carried out using 2 methods, the Purchase Method and also the Pooling of Interest method. The difference between the two lies in the assessment of an asset, whether there is an increase or decrease, which will later be calculated to determine the value of the asset or liability, or what is called goodwill, whereas for pooling of ownership, there is no goodwill because all companies are considered the same or equivalent. From this research it was found that Goodwill recognition due to business mergers, especially those that occurred in Indonesia, has been implemented by several companies. Goodwill is recorded in the Company's consolidated balance sheet separately. The Company considers various aspects, one of which is the controlling and non-controlling interests in the Company.